Bone tissue engineering using 3‐D polycaprolactone/gelatin nanofibrous scaffold containing berberine: In vivo and in vitro study. (2nd November 2021) - Ehterami, Arian; Abbaszadeh‐Goudarzi, Ghasem; Haghi‐Daredeh, Saeed; Niyakan, Maryam; Alizadeh, Morteza; JafariSani, Moslem; Atashgahi, Mahboubeh; Salehi, Majid
Abstract: A solid structure similar to an extracellular matrix network is needed for bone cells attachment and starting healing of bone damages. Different biomaterials and fabrication techniques are used for scaffold fabrication to prepare a supportive structure in bone tissue engineering. In the current study, a 3‐D polycaprolactone (PCL)/gelatin scaffold was developed by blending electrospinning and freeze‐drying techniques to make an appropriate structure for bone healing. In addition, different concentrations of berberine that have a positive effect on bone healing were loaded to enhance the healing process. Fabricated scaffolds were characterized by different tests like surface morphology, water contact angle, degradation rate, compressive strength, porosity, and Fourier transform infrared. Their interactions with blood and cells were evaluated by hemolysis, and MTT test, and the healing process was also evaluated by implanting scaffolds in the rat calvaria defect model. Based on the results, the average porosity of scaffolds was about 80% and by adding berberine, mechanical strength decreased while due to its hydrophilic properties, degradation rate increased. In vivo and in vitro tests showed better cell proliferation and bone healing in PCL/gelatin/berberine 0.1%‐treated group. These results showed the positive effect of fabricated scaffold on osteogenesis and bone healing and the possibility of using it in clinical trials.